Genome-Wide Association Studies and Haplotype-Sharing Analysis Targeting the Egg Production Traits in Shaoxing Duck - Xu, Wenwu; Wang, Zhenzhen; Qu, Yuanqi; Li, Qingyi; Tian, Yong; Chen, Li; Tang, Jianhong; Li, Chengfeng; Li, Guoqin; Shen, Junda; Tao, Zhengrong; Cao, Yongqing; et al. (Frontiers in Genetics, 2022)
Age at first egg (AFE), Egg number (EN) were economically-important traits related to egg production as it directly influences benefits of the poultry industry, but the molecular genetic research that affects those traits in laying ducks is still poor, Our objective was to identify the genomic regions and candidate genes associated with AFE, egg production at 43 weeks (EP43w) and egg production at 66 weeks (EP66w) in a Shaoxing duck population using genome-wide association studies (GWAS) and haplotype sharing analysis. SNP-based genetic parameter estimates showed that the heritability was 0.15, 0.20 and 0.22 for AFE, EP43w and EP66w, respectively. Subsequently, three univariate GWAS for AFE, EP43w and EP66w were carried out independently. 24 SNPs located on chromosome 25 within a 0.01 Mb region that spans from 4.511 Mb to 4.521 Mb were associated with AFE, 33 SNPs associated with EP43w were in a strong linkage disequilibrium region spanning from 3.186 Mb to 3.247 Mb and 4.442 Mb to 4.446 Mb on chromosome 25, and two interesting genes ACAD8 and THYN1 that may affect EP43w in laying ducks. There are two confidence intervals that affect EP66w, i.e., a 2.412 Mb region that spans from 127.497 Mb to 129.910 Mb on chromosome 2 and a 0.355 Mb region that spans from 4.481 Mb to 4.837 Mb on chromosome 29, and CA2, GAMT may be the putative candidate genes. Our study also found some haplotypes significantly association with these three traits based on haplotype sharing analysis. Overall, this study was the first publication of GWAS on egg production in laying ducks and our findings will be helpful to provide some candidate genes and haplotypes to improve egg production performance based on breeding in laying duck. On the other hand, we learned from a method called bootstrap test for verifying the reliability of GWAS with small experimental samples, users can access at https://github.com/xuwenwu24/Bootstrap-test.